Comparison of virtual microscopy and real microscopy for learning oral pathology laboratory course among dental students - Julia Yu-Fong Chang; Tzu-Chiang Lin; Ling-Hsia Wang; Feng-Chou Cheng; Chun-Pin Chiang (Elsevier, 2021)
Background/Purpose: Virtual microscopy has been used for teaching general and oral pathology laboratory course for more than 10 years. This study aimed to share the learning experience of an oral pathology laboratory course using either the virtual microscopy with digitalized virtual slides (virtual slide learning) or real microscopy using traditional glass slides (glass slide learning) among dental students. Materials and methods: Thirty-eight undergraduate dental students who took the compulsory course entitled "oral pathology" in the School of Dentistry, National Taiwan University were included in this study. The questionnaires were filled and final test was taken by these students after finishing the teaching of oral pathology laboratory course using either virtual or glass slide learning. The data were collected and analyzed statistically. Results: Our results showed a significantly higher acceptance rate (all P-values < 0.001) and a significantly better histopathological diagnosis ability (P < 0.01) among dental students using the virtual slide learning than those using the glass slide learning for the oral pathology laboratory course. Conclusion: Virtual microscopy has many advantages over real microscopy in oral pathology laboratory course teaching. Based on the results of our study, we believe that the virtual microscopy with digitalized virtual slides may gradually replace the real microscopy with glass slides for the learning of oral pathology laboratory course. We foresee that the virtual microscopic images of the patients' specimens may be added in the patients' digital medical charts in addition to the images of computerized tomography, magnetic resonance imaging, and sonography in the future.